Knowledge and Practice of Postpartum Mothers Regarding Puerperal Sepsis Prevention - Nora Mansour Abdel-fattah; Entesar Fatouh Abdel-moniem; Rania Abd El-hak Eid Farrag (Indonesian Journal of Global Health Research, 2022)
Puerperal sepsis is an infection which arises from bacterial invasion of the genital organs during postpartum period. The aim of this study was to assess the knowledge and practice of postpartum mothers regarding puerperal sepsis prevention. A descriptive study was used. A purposive sample composed of 120 postpartum mothers. This study was conducted at Obstetrics and Gynecology Department in Tamia General Hospital at Fayoum city. three tools were used in data collection in the present study: Structured Interviewing Questionnaire, Knowledge of postpartum mothers regarding puerperal sepsis, and Practice of postpartum mothers regarding puerperal sepsis prevention. findings of the presenting study revealed that less than two thirds of the studied mothers had unsatisfactory knowledge regarding puerperal sepsis and more than half of them had unsatisfactory practice regarding puerperal sepsis prevention. According to the findings of the present study, less than two thirds of the studied mothers had unsatisfactory knowledge regarding puerperal sepsis. Furthermore, more than half of them had unsatisfactory practice regarding puerperal sepsis prevention.